The seven deadly sins of White Christian nationalism : a call to action - Heyward, Carter (Religion in the modern world., 2022)
"Hear the call to overcome today's conservative rhetoric of hate and bring virtue back to Christian living... While right-wing conservatives dare to call themselves Christians as they tear down equality and justice, commit horrible acts of violence, and fan the flames of fascism in America, Carter Heyward issues a call to action for Christians to truly hear God's message of peace and love. This book attempts to show ways in which, through our highly privatized theologies and personal spiritualities, we American Christians have played a major role in building and securing structures of injustice in American life. Rising tides of white supremacy, threats to women's reproductive freedoms and to basic human rights for gender and sexual minorities, the widening divide between rich and poor, and increasing natural disasters and the extinction of Earth's species all point to a world crying out for God's wisdom. To move forward as followers of Jesus, we must first call out these ingrained cultural attitudes for what they are-the seven deadly sins of white Christian nationalism. We must commit ourselves to building a more perfect union in small personal ways and in large public acknowledgment of what the culture of white Christian nationalism is doing to our country and world"--